Kansei engineering approach for developing electric motorcycle - Baroroh, Dawi Karomati; Amalia, Mya; Lestari, Nur Puji (Communications in Science and Technology, 2019)
Electric vehicles are considered one of the solutions that can reduce vehicle emissions into the environment. However, the enthusiasts' number of the electric motorcycle is still relatively really low. In order to escalate product and competitive value in the market, the design elements of the electric motorcycle have to develop. The aim of this research is to design electric motorcycle that appropriate with user needs and desires by utilizing Kansei Engineering. This study involved 212 respondents for the Semantic Differential I and 204 respondents for the Semantic Differential II. The results of this study were 14 pairs of kansei words which were used to evaluate 11 sample designs where there were 5 items and 14 design categories. The design specifications of the most dominant electric motorcycle were angled seat, type 1 of front hood, 2 slots for luggage box, type 3 of headlight, and type 2 of body hood.